1998
DOI: 10.1161/01.str.29.3.722
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Microembolic Signals: A New Form of Cerebral Microembolism Presentation in a Patient With Middle Cerebral Artery Stenosis

Abstract: Background-Middle cerebral artery (MCA) stenosis is a rare occlusive disease in western populations, with a high risk of stroke recurrence. An artery-to-artery embolic mechanism has been argued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…In the chronic phase, Sliwka et al [6]could not detect MES in 58 patients with 78 MCA stenoses. Segura et al [7]described a patient with clusters of MES downstream to a recently symptomatic MCA stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the chronic phase, Sliwka et al [6]could not detect MES in 58 patients with 78 MCA stenoses. Segura et al [7]described a patient with clusters of MES downstream to a recently symptomatic MCA stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are only three reports in the literature on the presence and frequency of MES in patients with intracranial stenoses [5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…However, knowledge about embolism in patients with stenosis of the intracranial ICAs and MCAs is more limited. Recent studies show that HITS are often detectable in symptomatic patients with severe intracranial ICA and MCA stenosis [38,39,40]. Wong et al [38] used TCD to monitor for HITS in 114 patients with moderate or severe MCA stenosis diagnosed using MRA and TCD.…”
Section: Imaging and Ultrasound Monitoring Data Shows That The Prevalmentioning
confidence: 99%
“…Among symptomatic patients followed for an average of 13.6 months a significant association (log rank 5.96, p = 0.01) was found between the presence of HITS and further strokes [38, 39]. Segura et al [40] reported a patient with a high-grade MCA stenosis in whom ischemic symptoms correlated with clusters of HITS that occurred with a frequency of 8 clusters per hour with each cluster containing 12–45 microembolic signals.…”
Section: Imaging and Ultrasound Monitoring Data Shows That The Prevalmentioning
confidence: 99%
“…Nevertheless, others reported the coincidence of reduction rate of embolization in patients with acute stroke and therapy with warfarin plus antiplatelet [21] and, more recently, a paper reported the reduction of MES rate after receiving heparin in the acute phase of cardioembolic stroke [22] .…”
Section: Discussionmentioning
confidence: 99%